1988
DOI: 10.1111/j.1348-0421.1988.tb01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Outermost Layer Deficient Mutant Spores of Bacillus megaterium

Abstract: Outermost layer deficient mutant spores of Bacillus megaterium ATCC 12872 were isolated by Urografin density gradient centrifugation after mutagenesis with ethyl methanesulfonate. Although the composition of the cortex peptidoglycan was the same as that of the parent spores, three major proteins (48, 36, and 22 K daltons) were missing, suggesting that these proteins are components of the outermost layer. All mutant spores were also found to have very hydrophobic surface by 'salt aggregation test,' which would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The relative hydrophobicities of spores can be measured by a number of established techniques that include adherence to hydrocarbons (13,18,19,27), hydrophobic interaction chromatography (HIC) (7,10), salt aggregation (24), and contact angle measurements (14). To investigate the role of BclA in surface hydrophobicity, we compared spores with and without BclA (wild-type versus bclA mutant spores) in the bacterial adherence to hydrocarbon (BATH) assay as described previously by Rosenberg et al (18).…”
Section: Methodsmentioning
confidence: 99%
“…The relative hydrophobicities of spores can be measured by a number of established techniques that include adherence to hydrocarbons (13,18,19,27), hydrophobic interaction chromatography (HIC) (7,10), salt aggregation (24), and contact angle measurements (14). To investigate the role of BclA in surface hydrophobicity, we compared spores with and without BclA (wild-type versus bclA mutant spores) in the bacterial adherence to hydrocarbon (BATH) assay as described previously by Rosenberg et al (18).…”
Section: Methodsmentioning
confidence: 99%
“…We reported that galactosamine-6-phosphate polymer begins to be deposited on the forespore from t9 (17) and may be responsible for the surface hydrophobicity of the spore (22). In this study, it was indicated that this sugar polymer does not participate in the deposition of P36 and P22, but may play the role in protecting these OL proteins against the releasing factor after deposition, because loss of these proteins was not observed in the mature spore and the forespore at tio of the wildtype strain where the sugar polymer had been deposited.…”
Section: Discussionmentioning
confidence: 99%
“…The suspension (20 mg dry weight/ml deionized water) of spore coat preparation (18) was sonicated at 30-sec intervals for a total sonication time of 3 min with the small probe of a Heat Systems Ultrasonics sonicator, model W-220F, at 4 C. After sonication, the suspension placed on the tube containing the ten stepwise Urografin density gradients (density range, 1.28-1.37 g/cm3) was centrifuged as previously described (22). Two bands of density, 1.28 and 1.35 g/cm3, respectively, were collected by a syringe, washed with deionized water several times after centrifugation (10,000 x g for 20 min), and lyophilized after dialysis against deionized water for three days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations